Model of Empowerment to Improve Autonomy Directly Observed Treatment (DOT) Tuberculosis Patients - Syamilatul Khariroh; Oedojo Soedirham; Hamidah Hamidah; Endang Abdullah (Intelektual Pustaka Media Utama, 2016)
Empowerment as not yet optimal health promotion efforts done to enhance the autonomy of Directly Observed Treatment (DOT), which affect the success of the recovery of patients with pulmonary tuberculosis. The purpose of research was to develop a model empowerment based on Health Promotion and Health Literacy with approach to nursing intervention in an effort enhance the autonomy of the DOT - pulmonary TB patients. The method was an observational analytic with cross sectional approach. Multistage random sampling was DOT-pulmonary TB patients to decide the district and simple random sampling was assigned to choose the participants, a total of 253 DOT- pulmonary TB patients new case with acid resistant bacilli positive on the advanced phase in this study. The study conducted in five districts in Surabaya City (center, north, south, east and west). Data were collected by questionnaire on variables namely personal, cognitive and affective, nursing intervention, commitment, family supports, health literacy and DOT- autonomy. Structural Equation Modeling (SEM) with LISREL is used for constructing predictive model. Result : This study found a new model which was developed based on combination of Health Promotion Model (HPM) and Health Literacy (HL). Statistical result confirm that personal, cognitive and affective, health literacy and family support considered as important factors in improving DOT-autonomy. Conclusion : DOT- autonomy will improve by considering four main factors, personal, cognitive and affective, health literacy, family support. This model can be adapted by District Health Office Surabaya City as the main actor regional health development. In addition, this model may become a reference for other district in improving their nursing intervention in community setting.